Expectancy and Motivation: Determinants of Teacher Retention in Private Schools in Nepal - Shishir Sharma Neupane (The Open University of Sri Lanka, 2023)
Teacher retention has been a crucial issue in the higher education sector in Nepal. One primary problem associated with high turnover of teachers in educational institutes is the issue of effective delivery content of an educational program; and another is the loss of in terms of time and financial resources. This study aims to find the relation between retention factors and teacher retention in private schools in a region of Nepal. Vroom's expectancy theory and Herzberg's motivation theory are used to relating the expectancy of the teachers and select the appropriate factors for motivation by the schools. This study is based on a quantitative research design. A structured survey questionnaire was applied to the sample of teachers calculated from simple random sampling technique from 14 private secondary schools of Nepalgunj. Descriptive statistics, hypothesis tests and correlation analyses were carried out to explore teacher retention. The study revealed that salary and benefits, selection process, engagement, growth opportunities, work environment and leadership could predict teacher retention. In contrast, with a beta coefficient of 0.301, growth opportunities stand out as the most important factor that could predict teacher retention. The study recommends that private schools in Nepalgunj must attempt to understand the expectancy of teachers as per the Vroom's theory and also differentiate between hygiene and motivation factors as classified by Herzberg, which will give a clear understanding of the retention of the teachers. Thus, this study's results will benefit principals, school management, policymakers and further researchers.